2023
DOI: 10.3390/plants12071577
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Identification of Plant-Growth Inhibitory Constituents from Polygonum chinense Linn and Evaluation of Their Bioherbicidal Potential

Abstract: Polygonum chinense Linn. is a medicinal and invasive plant that belongs to the family Polygonaceae. The pharmacological activities and phytochemical constituents of Polygonum chinense are well reported, but the allelopathic effects and potent allelopathic substances of P. chinense remain to be investigated. Hence, this experiment was conducted to separate and characterize potentially allelopathic substances from an extract of the Polygonum chinense plant. The Polygonum chinense plant extracts highly suppressed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 58 publications
0
4
0
Order By: Relevance
“…Additionally, the I 50 values for the cress, lettuce, barnyard grass, and timothy shoot and root growth differed, indicating that inhibition via the C. oblongifolius extracts is species-dependent (Table 1). Similar outcomes of dose-and species-dependent inhibitory effects have been shown for extracts of Marsdenia tenacissima, Garcinia Xanthochymus, Polygonum chinense, and Anredera cordifolia [33][34][35][36]. Thus, the inhibitory activity of the C. oblongifolius extracts on the growth of the four examined plant species suggests that its extracts may possess phytotoxic substances.…”
Section: Discussionsupporting
confidence: 72%
“…Additionally, the I 50 values for the cress, lettuce, barnyard grass, and timothy shoot and root growth differed, indicating that inhibition via the C. oblongifolius extracts is species-dependent (Table 1). Similar outcomes of dose-and species-dependent inhibitory effects have been shown for extracts of Marsdenia tenacissima, Garcinia Xanthochymus, Polygonum chinense, and Anredera cordifolia [33][34][35][36]. Thus, the inhibitory activity of the C. oblongifolius extracts on the growth of the four examined plant species suggests that its extracts may possess phytotoxic substances.…”
Section: Discussionsupporting
confidence: 72%
“…The above plant parts extracts of Polygonum chinense (Chinese knotweed) significantly inhibited the growth of alfalfa and Italian ryegrass ( Figure 2 ). Our previous experiment revealed that P. chinense plant extracts inhibited four test plants (cress, lettuce, timothy, and barnyard grass) [ 37 ]. The inhibitory effects of the plant extracts against the test plants increased with increasing extract concentration.…”
Section: Discussionmentioning
confidence: 99%
“…Isolating and identifying secondary metabolites from natural sources (plants) is crucial for the development of ecologically friendly natural herbicides. In our previous experiment, two active compounds, (-)-3-hydroxy- β -ionone and (-)-3-hydroxy-7,8-dihydro- β -ionone, were isolated and identified from P. chinense plant extracts, and both identified compounds significantly retarded the seedling growth of cress [ 37 ]. In the present study on the P. chinense above plant parts extracts, two other active compounds were purified and characterized as dehydrovomifoliol ( Figure 6 ) and loliolide ( Figure 8 ) using several chromatographic methods ( Figure 3 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…17). 111) These compounds suppressed the growth of Lepidium sativum at concentrations of 0.01 mM and 1 mM for compounds 30 and 31, respectively, and the IC 50 values on the growth of L. sativum were 0.05 mM and 0.42 mM for compounds 30 and 31, respectively. The allelopathic activity of compound 30 was 8-fold greater than that of compound 31.…”
Section: Polygonum Chinensementioning
confidence: 93%